If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.75x + 8 = x Reorder the terms: 8 + 0.75x = x Solving 8 + 0.75x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8 + 0.75x + -1x = x + -1x Combine like terms: 0.75x + -1x = -0.25x 8 + -0.25x = x + -1x Combine like terms: x + -1x = 0 8 + -0.25x = 0 Add '-8' to each side of the equation. 8 + -8 + -0.25x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -0.25x = 0 + -8 -0.25x = 0 + -8 Combine like terms: 0 + -8 = -8 -0.25x = -8 Divide each side by '-0.25'. x = 32 Simplifying x = 32
| 0=x*2-x-30 | | -6=y+3 | | 10+4x=-14+6x | | 15b^2+10b-8=0 | | .75x+8=f(x) | | u-5=-8 | | sin(4x)=1 | | 5=-21+3t | | 6+w=-2 | | (7x+4)(3x+9)= | | y=226-33x | | -36+6x=12 | | 3.6x+8=26 | | n-10=-27 | | 1.25g+4=13.5 | | a^2-x=0 | | 12-4h=6 | | j-(-17)=30 | | 5-3*x=20 | | t+13.4=-4.5 | | 1p-5=8 | | 4(p+5)=7 | | 36t^2=9 | | -6n+5n=-3 | | 4(p+-5)=7 | | (6x-6)(4x+9)=0 | | -6r+5s+2t=-11 | | 3(x)=8.25 | | 3x^2-6x+4y^2-13=0 | | 12(y+2)=36 | | 8(x)=8.25 | | 8x+7=127 |